Examining the Effect of Perceived Price Fairness on Revisit Intention of Local Guests Sharia Hotel: Customer Satisfaction as Mediation - Mariyanti, Eka; Husin, Nor Azilah; Wijaya, Riani Sukma; Sari, Puti Embun; Putri, Siska Lusia; Abdilla, Mohammad; Putra, Ramadhani Kirana (Advances in Social Sciences Research Journal, 2023)
This paper aims to investigate the effect of Perceived Price Fairness on the Revisit Intention of sharia hotel guests in Padang City, as well as the mediating role of perceived Customer Satisfaction in the relationship between Perceived Price Fairness and Revisit Intention. This paper distributes questionnaires to sharia hotel guests located in the capital city of West Sumatra, namely the city of Padang. Respondents who filled out the questionnaire were Sharia hotel guests in sharia hotels. However, seeing the phenomenon in West Sumatra, especially the city of Padang, based on visit data from Syariah hotels, most guests staying at Syariah hotels were domestic tourists or local travelers from Pekanbaru and Jambi. Responses obtained from 241 sharia hotel guests were analyzed using Smart-PLS. In addition to analyzing the path coefficients, this study also examines the general method variance and the indirect effects of the relationship.The results show that perceived price fairness dramatically influences the level of customer satisfaction for Syariah hotel guests. Price is an effective strategy to promote guest behavioral intentions to revisit Syariah hotel guests. Better service quality is reflected in the Perceived Price Fairness issued by hotel guests in obtaining service. Hotel guests who receive poor service and poor hotel facilities will tend to compare the service with the costs incurred to ensure the appropriateness of the amount paid. In addition, customer satisfaction also influences the perception of sharia hotel guests to return to stay at sharia hotels. Practical implication – sharia hotel that wishes to implement Shariah-compliant hotel principles must improve hotel facilities and sharia-compliant hotel principles to reflect the Perceived Price Fairness offered. This is very important considering the relatively complex price structure in the follow-up of hotel selection, which can influence the patient’s decision on Revisit Intention.